Engagement of university professors in the COVID-19 Pandemic: influence of organizational support (Research, Society and Development, 2021)
This study aimed to identify the influence of organizational support on work engagement during the COVID-19 Pandemic. A survey was carried out with professors who work in higher education at the Federal University of Santa Maria. As analysis techniques, descriptive statistics, exploratory factor analysis and regression were used. It is identified that the adoption of the remote model generated an increase in work demands, in which, most professors, kept their focus despite the challenges in maintaining a positive state of mind. The organizational support offered by the institution directly influences the faculty's ability to remain engaged in this atypical and challenging situation. Thus, in emergency contexts, such as the COVID-19 Pandemic, it is essential that university managers provide adequate mechanisms in order to provide the necessary organizational support for teachers to remain engaged in the face of drastic and rapid changes in the context and form of teaching work.